Physical performance of the students of music schools compared with reference values - Apanowicz, Mateusz (Journal of Education, Health and Sport, 2018)
Introduction. Physical activity is the first method of treatment which prevents a great number of diseases. Material and methods. 393 students from randomly selected music schools in Poland and Germany were qualified for the study. The level of physical fitness was assessed by means of the Eurofit test in each of the schools. The obtained test results were confronted with reference levels. Conclusions 1. The level of the skills specific for musicians was significantly higher as compared with reference values. 2. The level of physical performance among musicians significantly differed from reference values.